Organizational justice for middle school principals in Wasit and its relationship to Career commitment from the teachers’ point of view - Naeem Radhawi, Saad (Journal of College of Education, 2021)
The current study was conducted to reveal the relationship between organizational justice for middle school principals in Wasit and job commitment from the teachers’ point of view, as well as determining the level of organizational justice and the level of job commitment for school principals, and the relational approach was adopted in the research. The research population reached (1739) teachers in the preparatory schools of the General Directorate of Education in Wasit Governorate. The research sample was randomly selected and the number of sample individuals reached (400) teachers. A questionnaire was adopted that included (19) items for organizational justice and a questionnaire for job commitment consisting of (20) items distributed between three areas, and the researcher made sure of their sincerity and consistency. The results of the research data were analyzed using the (SPSS) program, and the researcher came out with many conclusions, including that the degree of application of organizational justice for middle school principals in Wasit from the teachers’ point of view was high, and there were no statistically significant differences, according to the variables of sex, age, academic degree. And that the degree of career commitment was high for middle school principals, and based on the research findings, several recommendations were formulated.